2013
DOI: 10.1016/j.cell.2012.12.014
|View full text |Cite
|
Sign up to set email alerts
|

Reprogramming Adult Schwann Cells to Stem Cell-like Cells by Leprosy Bacilli Promotes Dissemination of Infection

Abstract: SUMMARY Differentiated cells possess a remarkable genomic plasticity that can be manipulated to reverse or change developmental commitments. Here, we show that the leprosy bacterium hijacks this property to reprogram adult Schwann cells, its preferred host niche, to a stage of progenitor/stem-like cells (pSLC) of mesenchymal traits by downregulating Schwann cell lineage/differentiation-associated genes and upregulating genes mostly of mesoderm development. Reprogramming accompanies epigenetic changes and rende… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

11
220
3

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 219 publications
(244 citation statements)
references
References 100 publications
(79 reference statements)
11
220
3
Order By: Relevance
“…In addition addition, glial cells show remarkable plasticity and are among the first cells to respond to injury or invasion by pathogens (72,73). Although at present EGCs are the least-studied peripheral glial cells in vertebrates, there is an increasing interest in understanding the complex roles of these cells in gastrointestinal physiology.…”
Section: Coordinate Development Of the Nervous And Lymphoid Systems Omentioning
confidence: 99%
See 1 more Smart Citation
“…In addition addition, glial cells show remarkable plasticity and are among the first cells to respond to injury or invasion by pathogens (72,73). Although at present EGCs are the least-studied peripheral glial cells in vertebrates, there is an increasing interest in understanding the complex roles of these cells in gastrointestinal physiology.…”
Section: Coordinate Development Of the Nervous And Lymphoid Systems Omentioning
confidence: 99%
“…In this respect it is interesting that in rodents, low levels of gliogenesis are detectable in the enteric ganglia of adult animals, raising the possibility that self-renewing glial progenitors of the ENS are used to generate progeny that replenish mEGCs eliminated during the natural turnover of the intestinal mucosa. The potential role of the microbiota and the mucosal immune system in the activation of glial progenitors and the homeostasis of EGCs is currently unclear, but it is interesting that other peripheral glial cells, such as Schwann cells, are capable of reprogramming to stem-like cells when challenged by leprosy bacteria, and that such reprogramming is thought to be mediated by the innate immune system (73,83). mEGCs appear to have additional and perhaps more direct effects on mucosal immunity.…”
Section: Microbiota Influence On Ens Developmentmentioning
confidence: 99%
“…This transformation creates a suitable environment for the bacteria to proliferate (7). More recently, it has been shown that further dedifferentiation leads to the reprogramming the Schwann cell to a "stem cell-like" cell with a plethora of new capabilities, such as redifferentiation into mesenchymal cells with the ability to spread infection or attracting macrophages to develop granulomas that could then serve as a Trojan horse for systemic dissemination of M. leprae (3,8). The presence of bacilli in the skin produces the dermatological manifestations of the disease, and nerve infection produces axonal dysfunction and demyelination, leading to sensory loss and its consequences of disability and deformity (2,9).…”
mentioning
confidence: 99%
“…The presence of bacilli in the skin produces the dermatological manifestations of the disease, and nerve infection produces axonal dysfunction and demyelination, leading to sensory loss and its consequences of disability and deformity (2,9). In this sense, the degenerative changes associated with infection of the peripheral sensory nerves are considered a crucial event in the natural history of HD (7,8). Once the infection is established, the occurrence of leprosy reactions, because of their inflammatory impact on peripheral nerves, remain an important contributor to sensory loss and dysfunction (9)(10)(11)(12).…”
mentioning
confidence: 99%
“…In leprosy, the lepromatous end of the spectrum is 11 times more likely to be associated with vitiligo than is tuberculoid leprosy 83 . It has been most recently demonstrated that Mycobacterium leprae alters the genetics of Schwann cells without even penetrating their nuclei and this activates genes that convert the cell into a neural crest stem cell, shielding the bacteria from destructive elements 84 . It has been questioned whether albinism could protect against leprosy, as they are not recorded together despite the fact that in Africa, both oculocutaneous albinism and, until recently, leprosy have high prevalence.…”
Section: Leprosymentioning
confidence: 99%